Artificial Intelligence in Indonesian Education: A Critical Review of Ethical Considerations, Implementation Challenges, and Educational Management Perspectives - Raharjo, Riris Setyaningrum; Rohmadi, Samsul Huda (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
This study critically reviews the ethics and challenges of Artificial Intelligence (AI) implementation in education in Indonesia, addressing a significant research gap concerning comprehensive, context-specific, and management-focused analyses. The primary purpose is to identify ethical dilemmas and practical challenges in AI integration within Indonesian educational settings and propose pragmatic solutions. Employing a descriptive qualitative approach with a critical literature review design, the study systematically analyzed academic literature and policy documents from Scopus, Google Scholar, and ERIC, published between 2020 and 2024. Data were meticulously analyzed using content and thematic analysis. Key findings reveal that while AI offers substantial potential for personalized learning and efficiency, its adoption in Indonesia is significantly hindered by pressing ethical concerns, including student data privacy vulnerabilities, the pervasive threat of algorithmic bias, and challenges to academic integrity. These ethical issues are compounded by substantial infrastructural disparities, particularly in remote regions, and a widespread deficit in digital literacy among educators and students. Furthermore, the research highlights critical educational management and policy gaps, characterized by a lack of comprehensive national strategies, clear institutional guidelines, and robust accountability mechanisms. The study concludes that successful AI integration in Indonesian education necessitates a holistic, integrated, and values-driven strategic management approach, emphasizing ethical governance, extensive capacity building, and robust policy formulation to ensure AI enhances human dignity and educational quality rather than exacerbating existing inequalities.